ANALISIS INVESTASI PADA PROYEK PEMBANGUNAN JALAN TOL PASURUAN - PROBOLINGGO (Jurnal Spesialis Teknik Sipil (JSpTS), 2022)
Toll roads are public roads that are part of the road network system and as national roads, for which users are required to pay tolls. The existence of toll roads is very important in the smooth flow of traffic along with the increasing amount of traffic caused by the increase in the number of vehicles and the condition of arterial road pavements that have been damaged (wavy and cracked) at several locations on the road and congestion that occurs due to damaged roads. damaged. The benefits of toll road operations are to influence regional development and economic improvement, as well as increase mobility and accessibility of people and goods, also provide benefits to users in the form of saving vehicle operating costs (BOK) and time compared to passing through non-toll roads, as well as providing returns on investment, maintenance, and toll road development for the Business Entities involved. One form of cooperation between the government and the private sector is the construction of the Pasuruan-Probolinggo (Paspro) Toll Road. Through the Toll Road Business Entity (BUJT) PT. Trans-Java Paspro Toll Road, the government cooperates in the construction of a 31 km toll road. PT. Trans-Java Paspro Toll Road received a 45-year concession to operate the toll road. The purpose of this study was to determine the investment feasibility of the Pasuruan-Probolinggo Toll Road based on the investment feasibility parameters of Net Present Value (NPV), Benefit Cost Ratio (B/C Ratio), Internal Rate Return (IRR), Payback Period (PBP), and determine the length of time. payback period (Payback Period) Pasuruan-Probolinggo Toll Road, and get a comparison of Vehicle Operating Costs (BOK) between Toll Roads and Arterial Roads. The final result of the analysis obtained that the NPV value was negative Rp. -1,773,803,000,000, and the IRR value is 9.56%, which is smaller than WACC = 13.07%, and the BCR value is less than 1.00, which is 0.763 so that it can be seen that the investment is not financially feasible for investors. However, BEP < 45 years concession period is April 2043, so it can be seen that it is still in the feasible category. The Vehicle Operational Cost (BOK) for arterial roads is Rp. 3,647/km for Goal I, Rp. 6,413/km for Gol II, Rp. 9,498/km for Gol III, Gol IV, and Gol V. Meanwhile, BOK for toll roads and added toll tariffs of Rp. 3.226/km for Goal I, Rp. 6,767/km for Gol II, Rp. 7,763/km for Gol III, Rp. 8.113/km for Gol IV and Rp. 8,463 for Gol V. From the analysis it is known that the cost of passing through the toll road is cheaper than going through the arterial road for all vehicle classes and is certainly very beneficial for toll road users.